Polar‐Electrode‐Bridged Electroluminescent Displays: 2D Sensors Remotely Communicating Optically. Issue 41 (12th September 2017) - Xu, Xiuru; Hu, Dan; Yan, Lijia; Fang, Shaoli; Shen, Clifton; Loo, Yueh‐Lin; Lin, Yuan; Haines, Carter S.; Li, Na; Zakhidov, Anvar A.; Meng, Hong; Baughman, Ray H.; et al.
Abstract: A novel geometry for electroluminescent devices, which does not require transparent electrodes for electrical input, is demonstrated, theoretically analyzed, and experimentally characterized. Instead of emitting light through a conventional electrode, light emission occurs through a polar liquid or solid and input electrical electrodes are coplanar, rather than stacked in a sandwich configuration. This new device concept is scalable and easily deployed for a range of modular alternating‐current‐powered electroluminescent light sources and light‐emitting sensing devices. The polar‐electrode‐bridged electroluminescent displays can be used as remotely readable, spatially responsive sensors that emit light in response to the accumulation and distribution of materials on the device surface. Using this device structure, various types of alternating current devices are demonstrated. These include an umbrella that automatically lights up when it rains, a display that emits light from regions touched by human fingers (or painted upon using a mixture of oil and water), and a sensor that lights up differently in different areas to indicate the presence of water and its freezing. This study extends the dual‐stack, coplanar‐electrode device geometry to provide displays that emit light from a figure drawn on an electroluminescent panel using a graphite pencil. Abstract : A new geometry is demonstrated for electroluminescent devices, which does not require transparent electrodes for energy input. Instead of emitting light through a conventional electrode, light emission occurs through a polar liquid or solid. These new devices act as remotely readable, spatially responsive sensors that emit light in response to the accumulation and distribution of materials on the device surface.